Lip Cream Formulation With Natural Dyes From Secang Wood Leather - Luluk Aniqoh Meliana; Juvita Herdianty; Arif Wijayanto (Universitas STRADA Indonesia, 2022)
Colorants are an important part of decorative cosmetics, including in lip cream preparations. Secang bark (Caesalpinia Sappan) contains chemical compounds of flavonoids, polyphenols, tannins and essential oils. Researchers formulate lip cream preparations by utilizing natural pigments contained in the bark of secang wood. The preparations were made with various concentrations of sappan bark extract, namely 15%, 20%, and 25%. Evaluation of the preparations made is an evaluation of physical quality including organoleptic tests, homogeneity, pH, spreadability, adhesion, smearing power, photostability, and stability tests by centrifugation method. Evaluation of safety was carried out through irritation test with patch test method and preference test. The results of the evaluation of lip cream preparations showed that all formulas had good greasing power and homogeneity, were physically stable which was characterized by no separation, and had good dispersibility, spreadability, and stable pH value. All preparations during storage for 21 days did not show changes in texture and odor. Then in terms of color, both organoleptically and photostability testing did not show a decrease in color intensity. Based on respondents' responses, the most preferred formula is formula II with the addition of an extract of 20%.